The Influence of Modified Anatomical Jendral Playing Cards in Improving Medical Student Learning Outcomes - Mokodoto, Randi; Yusuf, Muhamad Nur Syukriani; Daud, Serly; Paramata, Nanang Roswita; Wahjudi, Chairul (Jambura Medical and Health Science Journal, 2024)
Introduction: Human anatomy is a basic and challenging medical science studying the normal structure of the human body and its relationship with other body structures. However, the current anatomy learning methods must continue to be developed to make them better. This research aims to see the effect of modified anatomy Jendral playing cards on the results of the anatomical response of the musculoskeletal system in medical students.Method: This research was carried out at the Faculty of Medicine, Universitas Negeri Gorontalo, on 31 first-year pre-clinical medical students consisting of 7 men and 24 women with an average age of 18 years. The research design used is a pre-experiment method with one group pretest-posttest design where respondents will be given an intervention by playing Modified Jenderal Anatomy Playing Cards. Analysis of this research data used the Wilcoxon Test.Results: There was an increase in quiz results from 8,00 ± 12,00 (median ±interquartile range) to 36.00 ± 24.00 (median ±interquartile range), as well as the p-value of 0.000 (p-value ≤0.05).Conclusion: Playing modified anatomical jendral playing cards influences the results of medical students' Anatomy of Musculoskeletal System Practical Response Assessment. Medical teachers will use the present learning media innovation in activities reviewing anatomy practicum and using pictures Cadaver, which will be assessed to improve medical students' learning outcomes. Key words: Anatomy assessment results, anatomy cards, learning media, medical students